1998
DOI: 10.1029/98jd00083
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic particles can activate at lower relative humidity than slightly hygroscopic ones: A Köhler theory incorporating surface fixed charge

Abstract: Abstract. A number of laboratory experiments indicate that hydrophobic carbonaceous particles activate at lower supersaturations than is predicted by KOhler theory. Since a significant fraction of the global energy balance uncertainty is due to the so-called indirect effect, that of clouds, quantifying which particles activate is crucial to accurate prediction of climate. Most material surfaces obtain a fixed charge in water, and this is the case for many materials found in atmospheric aerosols. This fixed cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Especially, atmospheric fine particles (PM 2.5 , particles with an aerodynamic diameter of 2.5 m or less), have been found to play an important role in global climate change (Charlson et al, 1992;Wexler & Ge, 1998), human health problem (Dockery & Stone, 2007;Norris et al, 1999;Ostro, Broadwin, Green, Feng, & Lipsett, 2006;Schwartz, Dockery, & Neas, 1996) and visibility degradation (Chan et al, 1997;Chow et al, 1996;Sisler & Malm, 1994). Major components of PM 2.5 , reported as sulfate (SO 4 2− ), nitrate (NO 3 − ), ammonium (NH 4 + ), organic carbon (OC) and elemental carbon (EC), were the significant causes of visibility degradation (Cao et al, 2007;Chan et al, 1997;Chow et al, 1996;Conner, Bennett, Weathers, & Wilson, 1991;Tanner, Parkhurst, Valente, & Phillips, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, atmospheric fine particles (PM 2.5 , particles with an aerodynamic diameter of 2.5 m or less), have been found to play an important role in global climate change (Charlson et al, 1992;Wexler & Ge, 1998), human health problem (Dockery & Stone, 2007;Norris et al, 1999;Ostro, Broadwin, Green, Feng, & Lipsett, 2006;Schwartz, Dockery, & Neas, 1996) and visibility degradation (Chan et al, 1997;Chow et al, 1996;Sisler & Malm, 1994). Major components of PM 2.5 , reported as sulfate (SO 4 2− ), nitrate (NO 3 − ), ammonium (NH 4 + ), organic carbon (OC) and elemental carbon (EC), were the significant causes of visibility degradation (Cao et al, 2007;Chan et al, 1997;Chow et al, 1996;Conner, Bennett, Weathers, & Wilson, 1991;Tanner, Parkhurst, Valente, & Phillips, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Their study was limited to a system involving only sodium dodecyl sulfate and NaCl solute. A modification of the Köhler equation to include surface fixed charge was proposed by Wexler and Ge [1998]. They concluded that in a laboratory setting, surface charges on pure hydrophobic particles could cause growth and activation that are probably not relevant to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold of nucleation substantially decreases when water interacts (adsorbs) onto slightly soluble particles giving rise to the process of adsorption activation (Sorjamaa and Laaksonen, 2007;Henson, 2007). Henson (2007) showed that a number of existing adsorption models (e.g., Fletcher, 1958;Wexler and Ge, 1998) for slightly soluble and insoluble particles can be successfully applied to represent droplet formation from adsorption activation. Similarly, Sorjamaa and Laaksonen (2007) used the Frenkel-Halsey-Hill (FHH) multilayer physical adsorption model to describe water uptake as a function of relative humidity (i.e., water activity) and applied the theory to describe the activation of perfectly wettable and insoluble hydrophilic CCN.…”
Section: Introductionmentioning
confidence: 99%